Clinical Findings of COVID-19 Patients Admitted to Intensive Care Units in Guangdong Province, China: A Multicenter, Retrospective, Observational Study - Xu, Yonghao; Xu, Zhiheng; Liu, Xuesong; Cai, Lihua; Zheng, Haichong; Huang, Yongbo; Zhou, Lixin; Huang, Linxi; Ling, Yun; Deng, Liehua; Li, Jianwei; Chen, Sibei; et al. (Frontiers in Medicine, 2020)
Background: Information about critically ill patients with COVID-19 in China but outside of Wuhan is scarce. We aimed to describe the clinical features, treatment, and outcomes of patients with COVID-19 admitted to the intensive care unit (ICU) in Guangdong Province. Methods: In this multi-centered, retrospective, observational study, we enrolled consecutive patients with COVID-19 who were admitted to seven ICUs in Guangdong Province. Demographic data, symptoms, laboratory findings, comorbidities, treatment, and outcomes were collected. Data were compared between patients with and without intubation. Results: A total of 45 COVID -19 patients required ICU admission in the study hospitals (mean age 56.7 + 15.4 years, 29 males [64.4%]). The most common symptoms at onset were fever and cough. Most patients presented with lymphopenia and elevated lactate dehydrogenase. Treatment with antiviral drugs was initiated in all patients. Thirty-six patients (80%) developed acute respiratory distress syndrome at ICU admission, and 15 (33.3%) septic shock. Twenty patients (44.4%) were intubated and 10 (22.2%) received extracorporeal membrane oxygenation. The 60-day mortality was 4.4% (2 of 45). Conclusion: COVID-19 patients admitted to ICU are characterized by fever, lymphopenia, acute respiratory failure, and multiple organ dysfunction. The mortality of ICU patients in Guangdong Province was relatively low with a small sample size.